A critique of the participation norm in marine governance: Bringing legitimacy into the frame. Issue 126 (December 2021) - Fudge, Maree; Alexander, Karen; Ogier, Emily; Leith, Peat; Haward, Marcus
Abstract: Citizen and stakeholder participation is held to bolster the democratic legitimacy of. marine governance by building trust in the decision-making system through inclusion.However, a growing body of literature points to increasing disillusionment and.exclusion, and thus decreased legitimacy. In this study we apply a 'legitimacy lens' to.examine a dominant conceptualisation of participation in marine governance. We.argue that the social-ecological systems paradigm (SES) exerts a substantial.intellectual influence within marine governance. We identify that an ontological.underpinning of the conceptualisation of participation within this paradigm results in the.absence of a coherent articulation of democratic legitimacy in marine governance.scholarship. We suggest that the development of a more nuanced and overt account of.democratic legitimacy is necessary to strengthening the application of SES-informed.marine governance practices Highlights: We present a novel analytic lens to examine legitimacy in governance arrangements. Participation in marine governance is ruled by a social-ecological systems frame. The social-ecological systems framing of participation lacks democratic legitimacy.